The Effect of Content Marketing and Ewom on Purchase Intention and Brand Image - Martha, Haryadi Lisya; Nuryakin, Nuryakin; Arni, Arni (Universitas Muhammadiyah Sorong, 2024)
This study aims to determine the effect of content marketing on e-wom and its impact on purchase intention. The subjects in this study were social media followers on the official accounts of several shoe brands circulating in Indonesia. The sampling technique used purposive sampling by using several criteria. The number of samples in this study was 325. Data were collected using a questionnaire with a Liker scale of 1 to 5 and will be analyzed using the Structural Equation Modeling method. Based on the results of the analysis that has been carried out, it shows that content marketing has a significant positive effect on e-wom, e-wom has a significant positive effect on brand image and purchase intention, and brand image has a significant positive effect on purchase intention, and brand image is able to play a role. as a mediator between e-wom and purchase intention. In conclusion, this study accepts all the hypotheses that have been proposed.